Blue Economy: Perspektif dalam Peningkatan Nilai Ekonomi Indonesia - Ella Rahmayanti; Irne Aryanie; Munawarah; Imam Malik; Ghina Adhha Haura (Program Studi Akuntansi Fakultas Ekonomi Universitas Samudra, 2025)
ABSTRACT This study aims to evaluate the implementation of marine economic management policies in Indonesia and identify the obstacles in their application, as well as to formulate recommendations for improving economic value through the integration of the blue economy concept into the marine economic policy framework of Indonesia. The government is expected to implement the blue economy concept in Indonesia to enhance opportunities for increasing the economic value of the community, especially coastal communities. This study employs a descriptive analysis approach and a literature review. In the implementation process, the government is urged not to disregard the customs of local residents to ensure the preservation of the environment and traditions. The results of the literature review show that the blue economy offers solutions for developing the economy sustainably while maintaining the health of the ocean and its ecosystems. However, its implementation in Indonesia faces various challenges, including unsustainable exploitation of marine resources, socio-economic inequality, and a lack of attention to the social role of the oceans. This study emphasizes the need for collaboration among stakeholders, technological innovation, and comprehensive policies to overcome these challenges and optimize the potential of the blue economy in enhancing Indonesia's economic value sustainably ABSTRAK Penelitian ini bertujuan untuk mengevaluasi implementasi kebijakan pengelolaan ekonomi kelautan di Indonesia dan mengidentifikasi kendala-kendala dalam penerapannya, serta menyusun saran perbaikan untuk meningkatkan nilai ekonomi melalui pengintegrasian konsep blue economy ke dalam kerangka kebijakan ekonomi kelautan Indonesia. Pemerintah diharapkan dapat menerapkan konsep blue economy di Indonesia untuk meningkatkan peluang untuk peningkatan nilai ekonomi masyarakat, terutama masyarakat pesisir. Penelitian ini menggunakan pendekatan analisis deskriptif dan tinjauan pustaka. Dalam proses penerapannya, pemerintah dihimau untuk tidak mengesampingkan adat penduduk lokal agar kelestarian lingkungan dan adat terjaga. Hasil tinjauan literatur menunjukkan bahwa blue economy menawarkan solusi untuk mengembangkan perekonomian secara berkelanjutan dengan tetap menjaga kesehatan laut dan ekosistemnya. Namun, implementasinya di Indonesia menghadapi berbagai tantangan, termasuk eksploitasi sumber daya laut yang tidak berkelanjutan, ketidaksetaraan sosial-ekonomi, dan kurangnya perhatian terhadap peran sosial lautan. Penelitian ini menekankan perlunya kolaborasi antar pemangku kepentingan, inovasi teknologi, dan kebijakan yang komprehensif untuk mengatasi tantangan tersebut dan mengoptimalkan potensi blue economy dalam meningkatkan nilai ekonomi Indonesia secara berkelanjutan.